The Landed Theory of Profit - Loria, Achille (Quarterly Journal of Economics, 1891)
Journal Article The Landed Theory of Profit Get access Achille Loria Achille Loria University of Siena, Italy, 1891 Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 6, Issue 1, October 1891, Pages 108–111, https://doi.org/10.2307/1882168 Published: 01 October 1891